Pill testing or drug checking in Australia: Acceptability of service design features - Barratt, Monica; Bruno, R.; Ezard, N.; Ritter, A. (Wiley-Blackwell Publishing Ltd., 2017)
INTRODUCTION AND AIMS: This study aimed to determine design features of a drug-checking service that would be feasible, attractive and likely to be used by Australian festival and nightlife attendees. DESIGN AND METHODS: Web survey of 851 Australians reporting use of psychostimulants and/or hallucinogens and attendance at licensed venues past midnight and/or festivals in the past year (70% male; median age 23 years). RESULTS: A drug-checking service located at festivals or clubs would be used by 94%; a fixed-site service external to such events by 85%. Most (80%) were willing to wait an hour for their result. Almost all (94%) would not use a service if there was a possibility of arrest, and a majority (64%) would not use a service that did not provide individual feedback of results. Drug-checking results were only slightly more attractive if they provided comprehensive quantitative results compared with qualitative results of key ingredients. Most (93%) were willing to pay up to $5, and 68% up to $10, per test. One-third (33%) reported willingness to donate a whole dose for testing: they were more likely to be male, younger, less experienced, use drugs more frequently and attend venues/festivals less frequently. DISCUSSION AND CONCLUSIONS: In this sample, festival- or club-based drug-checking services with low wait times and low cost appear broadly attractive under conditions of legal amnesty and individualised feedback. Quantitative analysis of ecstasy pills requiring surrender of a whole pill may appeal to a minority in Australia where pills are more expensive than elsewhere. [Barratt MJ, Bruno R, Ezard N, Ritter A. Pill testing or drug checking in Australia: Acceptability of service design features. Drug Alcohol Rev 2017;00:000-000].